Volumetric Survey Speed: A Figure of Merit for Transient Surveys. (23rd June 2016) - Bellm, Eric C.
Abstract: Time-domain surveys can exchange sky coverage for revisit frequency, complicating the comparison of their relative capabilities. By using different revisit intervals, a specific camera may execute surveys optimized for discovery of different classes of transient objects. We propose a new figure of merit, the instantaneous volumetric survey speed, for evaluating transient surveys. This metric defines the trade between cadence interval and snapshot survey volume and so provides a natural means of comparing survey capability. The related metric of areal survey speed imposes a constraint on the range of possible revisit times: we show that many modern time-domain surveys are limited by the amount of fresh sky available each night. We introduce the concept of "spectroscopic accessibility" and discuss its importance for transient science goals requiring followup observing. We present an extension of the control time algorithm for cases where multiple consecutive detections are required. Finally, we explore how survey speed and choice of cadence interval determine the detection rate of transients in the peak absolute magnitude–decay timescale phase space.